Logic Structure Determination (LSD) as a Computer Assisted Structure Elucidation (CASE) for Molecular Structure Determination of Cytotoxic Cembranoids from Soft Coral - Januar, Hedi Indra; Zamani, Neviaty Putri; Soedharma, Dedi; Chasanah, Ekowati (Squalen, Buletin Pascapanen dan Bioteknologi Kelautan dan Perikanan, 2016)
Indonesian tropical soft corals are valuable resources that produce pharmacological cytotoxic cembranoids. However, Â the manual structure determination in these compounds requires adequate knowledge of organic chemistry. This study presents the application of Logic Structure Determination (LSD) as a freeware Computer Assisted Structure Elucidation (CASE) for automatic molecular structure determination of cembranoid compounds from soft corals species. 12 Nuclear Magnetic Resonance (NMR) datasets of cytotoxic cembranoids were used to evaluate the accuracy of LSD in generating the possible structures. The results of this study shows that LSD generated numerous possible molecular structures as the data input files were only derived from 2D-NMR HMQC (Heteronuclear Multiple-Quantum Correlation), COSY (Homonuclear Correlation Spectroscopy), and HMBC (Heteronuclear Multiple Bond Correlation). The accuracy was significantly enhanced (only 2-4 possible cembranoid structures from each NMR dataset) with the addition of H2BC (Heteronuclear 2 Bond Correlation) experimental data. This may indicate that VLRC (Very Long-Range Correlations) significantly affects LSD capability. Furthermore, LSD with direct 2 bond NMR experimental data is a reliable CASE technique for cembranoid compounds identification. In general, this freeware-CASE has the potential to be applied Â on other types of small molecule compounds and may serves as a solution for elucidation bottleneck step in studies on Indonesian natural products.